Sosialisasi Pemanfaatan Taman Obat Keluarga (TOGA) dan Sosialisasi Dapatkan-Gunakan-Simpan-Buang (DAGUSIBU) Obat - Amran Nur; Ismail Rahman (Universitas Khairun, 2021)
Alternative medicine and health problems related to the use of drugs often occur in the community because they do not understand alternative traditional medicines and the use of good and correct medicines. The TOGA and DAGUSIBU drug utilization program can be the right solution to overcome this problem. From the discussions conducted with the community in the Marikurubu sub-district, Ternate City, information was obtained that in that area there had never been socialized about the benefits of Family Medicinal Plants (TOGA) and Dagusibu. The purpose of this service is to increase the knowledge of the Marikurubu community about how to manage family medicinal plants (TOGA) and to socialize how to get, use, store and dispose of good medicines. This activity was carried out by outreach to the public about TOGA and Dagusibu, especially drugs used for the treatment of Covid-19. The socialization activity went smoothly with enthusiastic participants in participating in the program, as seen by the many questions asked by the community before conducting the socialization activity the week before we planted plants with medicinal properties. With the activity of planting family medicinal plants and this socialization, the community can apply the knowledge that has been obtained to the environment and family